2022
DOI: 10.1002/ijc.33949
|View full text |Cite
|
Sign up to set email alerts
|

Downstream of the HOX genes: Explaining conflicting tumour suppressor and oncogenic functions in cancer

Abstract: The HOX genes are a highly conserved group of transcription factors that have key roles in early development, but which are also highly expressed in most cancers. Many studies have found strong associative relationships between the expression of individual HOX genes in tumours and clinical parameters including survival. For the majority of HOX genes, high tumour expression levels seem to be associated with a worse outcome for patients, and in some cases, this has been shown to result from the activation of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 173 publications
0
7
0
Order By: Relevance
“…Numerous studies have substantiated that hox proteins not only actively participate in modulating normal tissue development but also in the pathogenesis of diverse cancers. 7 , 8 The over-expression of HOX genes, as reported by Warrick et al, 6 has been implicated in the SLs morphological changes that can lead to significant deformation of the dermal-epidermal junction. Furthermore, recent research has revealed a novel role of HOX gene family reactivation in the process of aging.…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies have substantiated that hox proteins not only actively participate in modulating normal tissue development but also in the pathogenesis of diverse cancers. 7 , 8 The over-expression of HOX genes, as reported by Warrick et al, 6 has been implicated in the SLs morphological changes that can lead to significant deformation of the dermal-epidermal junction. Furthermore, recent research has revealed a novel role of HOX gene family reactivation in the process of aging.…”
Section: Discussionmentioning
confidence: 92%
“…Many Hox genes are implicated in some form of cancer, in that constitutive expression seems to be a marker of worse survival, although some Hox genes seem to be protective in epithelial cancers, so the effects are likely cancer tissue type-specific and Hox-specific. HoxA3 in particular seems to have few associations to worsened cancer 49 .…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, for a subset of these hypermethylated genes methylation positively correlated with gene expression. Many of these hypermethylated, upregulated genes belonged to the family of developmental transcription factors [57] and have been previously implicated in breast cancer etiology and the development of endocrine resistance [58], including GATA2 [59], HOXC4 [60], HOXB13 [61], HOXC13 [62], MNX1 [63], OTX1 [64], PAX7 , SOX2 [65] and WT1 [66]. Notably, one of the 12 AI DMSs associated with HOXC4 was included in both AI models.…”
Section: Discussionmentioning
confidence: 99%